Clinical Studies of Sweet Bee Venom to The Effect of Abdominal Fat Accumulation - Lim, Chung-San (Journal of Pharmacopuncture, 2008)
Objective The purpose of this study was to investigate the effects of Sweet Bee Venom to the abdominal fat accumulation clinically. Methods The 20 healthy women volunteers who showed the notice of this study by the home page of Sangji University were treated with Sweet Bee Venom(SBV) during twenty times. To investigate the effects of Sweet Bee Venom of the abdominal fat accumulation, abdominal CT, LFT, Thermography, BMI, Inbody 3.0 etc. were performed during clinical trials. And statistical analysis was carried out the data of 10 volunteers who performed all the schedule of this study. Results Following results were obtained from the clinical studies Sweet Bee Venom showed the effect of decreased the body weight, thickness of abdominal skin and fat layer, BMI, and increased abdominal heat, but they are not showed statistical significant. Conclusions These results suggest that treatment Sweet Bee Venom on the abdomen was effective to decrease fat tissue but for the treatment of obesity was performed with right diet program and exercise.